Effect of geometrical parameters on the evaporative heat transfer and pressure drop of R-134a flowing in dimpled tubes - Aroonrat, Kanit; Asirvatham, Lazarus Godson; Dalkilic, Ahmet Selim; Mahian, Omid; Ahn, Ho Seon; Wongwises, Somchai (SPRINGER, 2021)
An investigation was experimentally performed to explore the influence of geometrical parameters on the evaporative heat transfer coefficient and pressure drop of R-134a in dimpled tubes. The test sections were the counter-flow tube-in-tube heat exchanger, where the refrigerant was evaporated in the inner tube and hot water flows in the annulus. Seven dimpled tubes with various helical pitches (p), dimpled pitches (z), and dimpled depths (e) were used as the test tubes. The test runs were carried out over mass fluxes of 300, 400, and 500 kg/m(2)s; heat fluxes of 20, 25, and 30 kW/m(2); and evaporating temperatures of 7, 10, and 13 degrees C. The results show the heat transfer enhancement factor (HF) and pressure drop penalty factor (PF) increase with a rise in e and a decrease in p and z. The HF and PF range between 1.03-1.7 and 1.76-9.00, respectively. The correlations for predicting the Nusselt number and the friction factor of R-134a during evaporation in dimpled tubes are proposed.
Keywords: Evaporation; Heat transfer; Pressure drop; Dimpled tube; HORIZONTAL SMOOTH; EMPIRICAL CORRELATIONS; NUMERICAL CORRELATION; GENERAL CORRELATION; CONDENSATION; PERFORMANCE; R-600A; R134A; Thermodynamics; Mechanics